Highly flexible, durable, UV resistant, and electrically conductive graphene based TPU/textile composite sensor - Zhou,Y; Stewart,R (Polymers for Advanced Technologies, 2022)
Flexible strain sensors have attracted considerable attention due to their applications in wearable monitoring fields such as human-computer interaction systems, athletic training, and health systems. Textiles are a desired substrate for fabricating wearable flexible sensors due to their light weight, comfort, and flexibility. However, the compatibility between textiles and conductive materials still faces critical challenges, especially for wearable sensors to achieve high sensitivity and a wide sensing range simultaneously with long-term monitoring stability, reliability, and wearing comfort. In this study, we propose a graphene-based TPU/textile composite sensor that can be produced using small-scale manufacturing techniques, using laser cutting combined with film coating and thermal transfer processes and further explore its mechanical, electrical, and sensing properties. Since the human body exhibits different magnitudes of motion and fabric sensors integrated into clothing would face multiple challenges in real world usage e.g. repetitive wear, sweat and sunlight exposure, we performed sensitivity, reliability and durability tests to further evaluate real world usage of the fabric sensors. The developed composite sensor exhibits a high sensitivity (GF = 498), wide sensing range (0%–293%), excellent reliability and stability which only shows 5% deviation after 10,000 cycles of stretching under 5% strain. In addition, the graphene-based textile composite sensor thermalised by TPU film can also maintain high stability after long-term UV irradiation and multiple washing cycles. When integrated into various wearable devices, our composite sensor can detect a wide range of human body motions accurately, as well as subtle physiological signals, exhibiting great potential in incorporating into wearable monitoring devices.